Factores de riesgo que inciden en el desarrollo de pancreatitis aguda de origen biliar en pacientes de 40 a 50 años en el Hospital General IESS de Ceibos y Guasmo Sur 2019 – 2022 - Rentería Rodas, Valeria Estephania (2022)
Introduction Acute pancreatitis is an abrupt and reversible inflammatory process of the pancreatic parenchyma that can cause a systemic inflammatory response, organ failure, which can even lead to death. Objective To identify the risk factors in the development of acute pancreatitis of biliary origin in patients aged 40 to 50 years at the IESS General Hospital in Ceibos and Guasmo Sur from January 2019 to August 2022. Methodology A universe of 500 patients was collected, among which 134 were outside the age range we required, 140 did not enter the required study because they did not meet all our inclusion criteria. Thus, leaving a sample of 226 patients for the study with the respective ICD-10. Results The 154 patients with acute pancreatitis of biliary origin, 103 patients were women (66.9%) and 51 patients were men (33.1%). Our studied base presents a relationship with the analyzed bibliographical references that has a higher prevalence in women, however, gender is not considered a risk factor. Conclusion In our work, the risk factors that we were able to identify are mostly modifiable, such as an unhealthy diet that can trigger a set of metabolic disorders that can cause acute pancreatitis of biliary origin, in addition to hypercalcemia and hypertriglyceridemia